2016
DOI: 10.1177/1744987116678904
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analysis of the factors that shape adult nursing students' values, attitudes and perceptions of compassionate care

Abstract: Nursing students are the future of nursing and are situated between the expectation of the public: that they will receive compassionate care, and the profession: that it will continue to develop technically to meet the needs of the changing healthcare economy. Research has focused on the factors affecting registered nurses' values in care, however, less is known regarding the factors that shape nursing students' values, attitudes, and perceptions of compassionate care. Six focus group discussions with 23 adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…How best to help students develop the motivation and skills for compassionate care, however, remains uncertain. While authors agreed that compassion can be learned (Elsden, ; Geraghty, Lauva, & Oliver, ; McSherry et al., ), how that learning is accomplished has not been empirically determined. One international survey of 1,323 nurses, students, educators, and managers from 15 countries showed that 73% of nurses receive an inadequate level of teaching for improving compassionate care (Papadopoulos et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…How best to help students develop the motivation and skills for compassionate care, however, remains uncertain. While authors agreed that compassion can be learned (Elsden, ; Geraghty, Lauva, & Oliver, ; McSherry et al., ), how that learning is accomplished has not been empirically determined. One international survey of 1,323 nurses, students, educators, and managers from 15 countries showed that 73% of nurses receive an inadequate level of teaching for improving compassionate care (Papadopoulos et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…If you would like a copy of this report, please contact the authors directly. The main findings from this evaluation were published in two phases: (1) Kevern and Hill (2014); The fourth study featured a cross-sectional analysis of adult nursing students' values, attitudes and perceptions of compassionate care (McSherry, Bloomfield et al, 2016). A total of 22 students' understanding of personal and professional values were explored in six focus groups, along with identification of factors that shaped these values, and whether they influenced their ability to provide compassionate care.…”
Section: Overview Of the Studiesmentioning
confidence: 99%
“…First-year adult nursing student (focus group age range: 28-44 years). Study 4: Cross-sectional analysis (McSherry, Bloomfield et al, 2016).…”
Section: Realising Human Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…[86] Recent data suggests that whilst only 10% of general nurses are male, [87] this figure rises to more than 38% in psychiatric nursing. [88] In response to the feminised nature of nurse training [89] and female-oriented descriptions of nursing care [90] there appears to be growing use of more gender-neutral psychiatric nursing terminology, with phrases such as 'nurturing', 'compassion' and 'sympathy' [5,86,87,91] being replaced by 'empowerment', 'facilitation' and 'empathy'. [36,84,92] Furthermore, psychiatric nurses now emphasise distinctive features determining their practice, including holism, the therapeutic relationship, person-centred approach and therapeutic use of self [38,93,94] and sometimes even occupy roles from which the term 'nurse' itself is absent.…”
Section: Language and Role Redefinitionmentioning
confidence: 99%